Coordination, Organizations, Institutions, and Norms in Agent Systems VI COIN 2010 International Workshops, COIN@AAMAS 2010, Toronto, Canada, May 2010, COIN@MALLOW 2010, Lyon, France, August 2010, Revised Selected Papers - Vos, Marina; Fornara, Nicoletta; Pitt, Jeremy V.; Vouros, George; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the thoroughly reviewed joint postprocessings of two international workshops on Coordination, Organization, Institutions and Norms in Agent Systems, COIN@AAMAS 2010, held in Toronto, Canada in May 2010 and COIN@MALLOW 2010, held in Lyon, France in August 2010. The 20 revised full papers presented went through several rounds of reviewing and revision and were carefully selected for presentations. The papers are organized in topical sections on normative systems design and modeling; social aspects; and norms at runtime: learning and enforcing.
Keywords: Computer science; Computer Communication Networks; Software engineering; Information systems; Artificial intelligence; Computer Science; Artificial Intelligence (incl. Robotics).; Software Engineering; Computer Communication Networks; Information Systems Applications (incl.Internet).; User Interfaces and Human Computer Interaction; Computers and Society